Perbedaan Tumbuh Kembang Antara Bayi Usia 6 Bulan yang Diberi ASI Eksklusif Dan Susu Formula - Asfian Asfian (Jurnal Vokasi Kesehatan, 2015)
Abstract: Differences In Growth Among Infants Aged 6 Months Who Were Breastfed Exclusively With Infants Aged 6 Months Who Were Given Formula Milk. The aims of this research were to determine differences in growth and development which include, weight, height, nutritional status, and psychosocial development among infants exclusively breastfed and formula milk. This research is an observational research with cross-sectional design, the number of samples is 60 infants (32 exclusively breastfed infants and 28 infants given formula) samples taken by random sampling. Collecting data through interviews and direct observation. Data analysis using univariate analysis, the bivariate statistical tests, and chi-square test. The results showed there’s no significant difference between weight, height, and nutritional status of infants that given exclusively breastfed to infants that given formula milk. There are significant differences between the psychosocial developments of infant age 6 months old who were given exclusively breastfed and formula milk (P=0,027)Abstrak: Perbedaan Tumbuh Kembang Antara Bayi Usia 6 Bulan Yang Diberi ASI Eksklusif Dan Susu Formula. Penelitian ini bertujuan untuk mengetahui perbedaan tumbuh kembang yang meliputi, berat badan, Tinggi Badan, Status Gizi, dan Perkembangan Psiko-sosial antara bayi yang diberi ASI Eksklusif dan Susu Formula. Penelitian ini bersifat observasional dengan desain Cross sectional, jumlah sampel 60 orang bayi (32 bayi ASI Eksklusif dan 28 bayi Susu Formula) sampel diambil secara random sampling. Pengumpulan data dengan wawancara dan observasi langsung. Analisa data menggunakan analisa  univariat, bivariat dengan uji statistik t test dan Chi-square. Hasil penelitian menunjukkan tidak ada.  perbedaan yang bermakna antara berat badan, tinggi badan dan status gizi bayi yang diberi ASI Eksklusif dengan bayi yang diberi Susu Formula. Ada perbedaan yang bermakna antara perkembangan Psiko-sosial bayi usia 6 bulan yang diberi ASI Eksklusif dengan Bayi usia 6 bulan yang diberi Susu Formula(P=0,027).